2018
DOI: 10.3390/tropicalmed3040125
|View full text |Cite
|
Sign up to set email alerts
|

Artemether and Praziquantel: Origin, Mode of Action, Impact, and Suggested Application for Effective Control of Human Schistosomiasis

Abstract: The stumbling block for the continued, single-drug use of praziquantel (PZQ) against schistosomiasis is less justified by the risk of drug resistance than by the fact that this drug is inactive against juvenile parasites, which will mature and start egg production after chemotherapy. Artemisinin derivatives, currently used against malaria in the form of artemisinin-based combination therapy (ACT), provide an opportunity as these drugs are not only active against malaria plasmodia, but surprisingly also against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 79 publications
0
43
1
Order By: Relevance
“…The high prevalence of intestinal schistosomiasis infection found in the current study and in the previously reported studies indicate an urgent need for targeted interventions in addition to the current mass praziquantel treatment program for prevention and control of schistosomiasis around the Lake Zone and other endemic settings in the SSA region. Re-evaluation of the preventive chemotherapy being deployed by the National NTD Control Programs in SSA including the mode of delivery of annual mass praziquantel treatment such as giving repeated praziquantel doses may be considered [40] or research on alternative regimens such as combining praziquantel with artemisinin-based combination therapy targeting both the adult and juvenile parasites is recommended [41]. Apart from preventive chemotherapy, the provision of clean and safe water, improvement in sanitation and hygiene, and practical health education to school-aged children and the community is equally important in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of intestinal schistosomiasis infection found in the current study and in the previously reported studies indicate an urgent need for targeted interventions in addition to the current mass praziquantel treatment program for prevention and control of schistosomiasis around the Lake Zone and other endemic settings in the SSA region. Re-evaluation of the preventive chemotherapy being deployed by the National NTD Control Programs in SSA including the mode of delivery of annual mass praziquantel treatment such as giving repeated praziquantel doses may be considered [40] or research on alternative regimens such as combining praziquantel with artemisinin-based combination therapy targeting both the adult and juvenile parasites is recommended [41]. Apart from preventive chemotherapy, the provision of clean and safe water, improvement in sanitation and hygiene, and practical health education to school-aged children and the community is equally important in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…The poor efficacy of praziquantel against juvenile schistosomes is well recognized, and hence, the need for further treatment optimization research is evident. To enhance praziquantel performance, randomized clinical trials (RCTs) to investigate the combination of praziquantel with other drugs that are active against the juvenile worms (such as artemisinins) [32], or the use of repeated praziquantel doses, may be considered in endemic settings [16,31].…”
Section: Discussionmentioning
confidence: 99%
“…PZQ is efficacious against adults matured parasites but is less effective against juvenile worms [14]. We hypothesized that combining ACTs with PZQ would complement and potentially add to the killing effect of both immature and matured stages of the parasite to prevent transmission as suggested previously [31,47]. Several ACTs exist, but DHP was chosen in this study due to its multifactorial advantages including: (i) DHP has not been extensively used for malaria treatment in Tanzania compared to other first-line antimalarial drugs such as ALU, (ii) costeffectiveness and easy schedule of DHP administration (once a day) compared to ALU and (iii) its long duration of post-treatment prophylaxis which will offer protection to children against malaria who remain to be a vulnerable population in SSA.…”
Section: Discussionmentioning
confidence: 93%